Examining The Excess Cash Holdings As An Indicator of Agency Problems - Hendrawaty, Ernie (International Business and Accounting Research Journal, 2020)
This research aims to examine the implications of excess cash holdings on firm value based on agency theory. Data were obtained from a total sample of 1828 non-financial public companies in Indonesia, with 672 exceeding normal cash holdings using the panel regression techniques. The result showed that excess cash holdings have a negative effect on the firm value which is stronger for more concentrated ownership, for more dispersed ownership and for more financially difficult firms. Overall the empirical finding showed that excess cash holdings acts as a significant indicator of agency problems.